ENTOMOPATHOGENIC NEMATODES ON CONTROL OF MEDITERRANEAN FRUIT FLY (DIPTERA: TEPHRITIDAE) - Rohde, Cristhiane (2020)
Mediterranean fruit fly (Ceratitis capitata) is one of the world's major pests infesting fruit crops, causing significant losses. However, this insect has a soil phase and is a potential target for entomopathogenic nematodes. The objective of this work was to test the efficiency of the nematodes Steinernema carpocapsae ALL and Heterorhabditis amazonensis JPM4 in controlling larvae and pupae of Ceratitis capitata. Petri dishes with filter paper or pots with 200 g of soil were used to assess different nematode concentrations; 20 individuals (larvae or pupae) were placed in each container and the nematode suspension was applied at concentrations of 0, 140, 180, 220, 260, and 300 IJs (infective juveniles) cm-2. The nematode horizontal movement was tested using pots with soil and a metal screen at every 10 cm to define different distances (0, 10, 20, and 30 cm from the application site). Ten larvae and ten pupae were transferred to every distance; 10 mL of the nematode suspension (220 IJs cm-2) were applied at the distance zero; 10 mL of the nematode suspension with 220 IJs cm-2 was applied to each pot, using ten larvae and ten pupae for each evaluation time (0, 10, 20, and 30 days after application of nematodes) to study the effectiveness of these nematodes over time. Both nematodes killed C. capitata larvae and pupae, but S. carpocapsae ALL was the most effective. However, this nematode showed no ability for horizontal movement, which was found in H. amazonensis JPM4 nematodes. Both nematodes showed decreasing efficiency over time.